Selective extraction of napins: Process optimization and impact on structural and functional properties. (January 2022) - Albe-Slabi, Sara; Defaix, Claire; Beaubier, Sophie; Galet, Olivier; Kapel, Romain
Abstract: There is a growing worldwide demand for alternative sources of proteins for human nutrition. In this context, many researches have been carried out to develop an original process for production of total proteins from rapeseed meal. Interestingly, some recent works have demonstrated a possible selective extraction of napins (rapeseed albumins). However, the precise impact of extraction conditions on process performances has never been elucidated. The aim of this study was to establish the optimal conditions for selective extraction of napins from rapeseed meal while producing a high-quality solid residue. First, the effect of pH (2–4) and NaCl concentration (0–0.2 mol.L −1 ) at 20 and 55 °C on the extraction process performances was investigated by design of experiments. Second, a rational approach of multicriteria optimization including genetico-evolutionary algorithm was employed. As a result, two sets of optimal conditions (pH 2.0/0.11 mol.L −1 of NaCl at 20 °C and pH 3.75/0.2 mol.L −1 of NaCl at 55 °C) were found. They allowed for >55% of napin extraction yield, >95% of napin proportion in the extract and <4% of phytic acid content in the solid residue. However, much greater yield of napins was noted at the higher extraction temperature (55.4% vs 75.56% at 20 and 55 °C, respectively). Napins extracted under the two optimal conditions and purified by ultrafiltration had a light creamy color and similar composition. Minor structural modifications between the two proteins were observed, but they did not affect the functional properties (foaming and emulsifying properties) that appeared to be comparable. Graphical abstract: Image 1 Highlights: Selective extraction of napins while producing a high-quality solid residue. Modeling of selective napin extraction process coupled with multicriteria optimization. Optimal conditions were pH 2/0.11 mol.L −1 NaCl/20 °C and pH 3.75/0.2 mol.L −1 NaCl/55 °C. Greater yield of napins observed at the higher extraction temperature (55 vs 20 °C). Napins extracted were light creamy, with high solubility and promising functionalities.